2014
DOI: 10.1128/aac.02995-14
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Extracellular Activities of Trimethoprim-Sulfamethoxazole against Susceptible and Multidrug-Resistant Mycobacterium tuberculosis

Abstract: We investigated the activity of trimethoprim-sulfamethoxazole (SXT) against Mycobacterium tuberculosis, the pathogen that causes tuberculosis (TB). The MIC distribution of SXT was 0.125/2.4 to 2/38 mg/liter for the 100 isolates tested, including multiand extensively drug-resistant isolates (MDR/XDR-TB), whereas the intracellular MIC 90 of sulfamethoxazole (SMX) for the pansusceptible strain H37Rv was 76 mg/liter. In an exploratory analysis using a ratio of the unbound area under the concentrationtime curve fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…1,3,5,[7][8][9] Although no breakpoint has been established for amikacin, a similar rate of isolates below 16 mg/l (80.8%) was found, in agreement with a previous study (85.9%). 7 For the remaining drugs, and in particular for rifampicin, ethambutol, linezolid, and moxifloxacin, most isolates had MICs beyond the reach of therapeutic doses based on what is suggested by PK/PD, clinical outcome, and MIC distribution data for MAC, 5,6,8 even if synergy is taken into account. The evidence on which such drugs are recommended for the initial treatment of MAC is unclear and this has been based in part on clinical trials involving HIV patients in the pre-antiretroviral therapy era.…”
Section: Discussionsupporting
confidence: 85%
“…1,3,5,[7][8][9] Although no breakpoint has been established for amikacin, a similar rate of isolates below 16 mg/l (80.8%) was found, in agreement with a previous study (85.9%). 7 For the remaining drugs, and in particular for rifampicin, ethambutol, linezolid, and moxifloxacin, most isolates had MICs beyond the reach of therapeutic doses based on what is suggested by PK/PD, clinical outcome, and MIC distribution data for MAC, 5,6,8 even if synergy is taken into account. The evidence on which such drugs are recommended for the initial treatment of MAC is unclear and this has been based in part on clinical trials involving HIV patients in the pre-antiretroviral therapy era.…”
Section: Discussionsupporting
confidence: 85%
“…The need for novel therapeutic agents to meet the challenge of MDR and XDR TB has renewed interest in these and other antifolates. Several reports indicate that the vast majority of clinical isolates of M. tuberculosis, including MDR and XDR strains, are susceptible to a combination of sulfamethoxazole and the diaminopyrimidine trimethoprim (29)(30)(31)(32)(33). In addition, PAS has recently been shown to be an antifolate prodrug (34)(35)(36).…”
Section: Folate Metabolism As a High-value Drug Targetmentioning
confidence: 99%
“…A recent structural study suggested that the Tyr100 residue in M. tuberculosis DHFR may be responsible for the weak binding of trimethoprim to M. tuberculosis DHFR and showed that a variant, Y100F, had increased affinity for trimethoprim (59). Despite this limited antitubercular activity of trimethoprim, several studies have demonstrated that combinations of trimethoprim and sulfamethoxazole are effective against drug-susceptible and MDR strains of M. tuberculosis (29)(30)(31)(32)(33)). An evaluation of synergy between these drugs showed that subinhibitory concentrations of sulfamethoxazole conferred a significant reduction of the MIC of trimethoprim (fractional inhibitory concentration index of 0.5) (31).…”
Section: Folate Metabolism As a High-value Drug Targetmentioning
confidence: 99%
“…As MDR/XDR-TB is notoriously difficult to treat, already approved drugs, such as trimethoprim-sulfamethoxazole, are being investigated as treatment options (1). The activity of penicillin against Mycobacterium tuberculosis was investigated in the 1940s (2), but ␤-lactams were deemed ineffective.…”
mentioning
confidence: 99%